BEYOND RITUAL EVALUATION: HAFLATUL IMTIHAN AS A MEANINGFUL EVENT OF COMMUNAL BECOMING IN PROBOLINGGO - Ilahiyah, Athiyah; Adawiyah, Robiatul; Choiriyah, Mahmadatul; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study explores Haflatul Imtihan at TPQ Tarbiyatul Quran Probolinggo, not merely as an academic examination mechanism, but as a meaningful event (Ereignis) that constitutes the community's spiritual world. While conventional sociological approaches often reduce such rituals to their functional roles as tools for education or social cohesion—this research adopts a Sociology of Ereignis framework to understand how the event discloses the lived religious experience of the participants. Through phenomenological engagement and reflexive observation, the study reveals that Haflatul Imtihan serves as a moment of mutual disclosure where the sacred (the Quran) and the social (the community) are intertwined. It is not just a test of memory, but a transformative event where the identity of the community is continuously re-enacted and the presence of the divine is felt as a shared reality. The findings suggest that true community empowerment emerges not from technical management, but from the authentic participation in these world-shaping events.